2006
DOI: 10.1007/s10461-006-9134-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, Hepatitis B, Syphilis, and Chlamydia Among Adults Seeking Treatment for a Mental Disorder in Southern India

Abstract: This study estimated the prevalence, and identified the correlates, of HIV, chlamydia, syphilis, and Hepatitis B among patients seeking treatment for a mental disorder in India. Patients (n = 948) submitted a blood sample for serologic testing and participated in a brief interview. Lifetime prevalence rates were nearly 2% for HIV, 10% for chlamydia, 3% for Hepatitis B, and 3% for syphilis; 15% of patients had evidence of at least one infection. Bivariate associations between infection status and patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
5
33
1
Order By: Relevance
“…Minor and who are unable to communicate verbally were excluded from the study Sample Frame: 10,100 (from the Register) Expected prevalence rate of HIV was taken as 12.5%, based on which Sample Size was calculated as 400 [taking into the Confidence level=99.99% and Confidence interval=±6. 30] Sample size was adjusted upward to allow for non-response and other factors. Incorporating 5% for possible non-participation and 5% for non-respondent the adjusted sample size turns out to be 440.…”
Section: Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Minor and who are unable to communicate verbally were excluded from the study Sample Frame: 10,100 (from the Register) Expected prevalence rate of HIV was taken as 12.5%, based on which Sample Size was calculated as 400 [taking into the Confidence level=99.99% and Confidence interval=±6. 30] Sample size was adjusted upward to allow for non-response and other factors. Incorporating 5% for possible non-participation and 5% for non-respondent the adjusted sample size turns out to be 440.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Few studies have examined the influence of depression on HIV risk in India. HIV prevalence is observed to range between 2% to 3% among people with depression, compared to 0.7% prevalence in the general population in India [30]. Sahay et al, [31] found that Indians who are engaged in high-risk behavior are almost 3 times more likely to be depressed and anxious.…”
mentioning
confidence: 99%
“…In a general hospital setting in South of India, HIV infection rate was 1.03% compared to the national seroprevalence rate of 0.7% [8][9][10][11][12]. HIV prevalence of 1.7% has been reported among psychiatric inpatients [13]. The predominant risk behavior among psychiatric patients in India is unprotected heterosexual intercourse, which is the most common mode of disease transmission in the country [14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4][5] Recent technological advances have facilitated early detection and treatment of CT infections. 2,4,[6][7][8][9] If left untreated, a CT infection may have severe consequences for infected people and their sexual partners as well as adverse pregnancy outcomes. 1,7,10 Health problems that have been attributed to CT infections include HIV=AIDS, infertility, pelvic inflammatory disease (PID), ectopic pregnancy, chronic pelvic pain, and testicular and prostate infections.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,[6][7][8][9] If left untreated, a CT infection may have severe consequences for infected people and their sexual partners as well as adverse pregnancy outcomes. 1,7,10 Health problems that have been attributed to CT infections include HIV=AIDS, infertility, pelvic inflammatory disease (PID), ectopic pregnancy, chronic pelvic pain, and testicular and prostate infections. 1 Vertical transmission of CT and other related STIs may also cause poor outcomes for newborn infants.…”
Section: Introductionmentioning
confidence: 99%